The bone marrow microenvironment is similarly impaired in allogeneic hematopoietic stem cell transplantation patients with early and late poor graft function - Kong, Y; Wang, Y-T; Hu, Y; Han, W; Chang, Y-J; Zhang, X-H; Jiang, Z-F; Huang, X-J (Bone marrow transplantation (Basingstoke), 2016)
Poor graft function (PGF), including early and late PGF, is a serious complication following allotransplant. We recently reported that bone marrow microenvironment abnormalities may occur in cases of late PGF. Whether these abnormalities occur in early PGF remains unknown. To answer this question, we performed a nested case–control study comparing cellular elements of the bone marrow microenvironment in 10 subjects with early PGF, 30 subjects with late PGF and 40 subjects without PGF. Bone marrow endosteal cells, perivascular cells and endothelial cells were analyzed by flow cytometry and by hematoxylin–eosin and immunohistochemical staining in situ . Subjects with early and late PGF had similar abnormalities in these cell types compared with transplant recipients without PGF. However, none of the aforementioned elements of the bone marrow microenvironment were significantly different between early and late PGF patients. Our data suggest that similar abnormalities in the bone marrow microenvironment may occur in early and late PGF post allotransplant. Cellular approaches, such as the administration of mesenchymal stem cells, promise to be beneficial therapeutic strategies in patients with early or late PGF.